Evidence that periweaning failure‐to‐thrive syndrome (PFTS) has a genetic predisposition. (6th June 2015) - Ramis, G.; Marco, E.; Magaña, V.; González‐Contreras, P.; Swierczynski, G.; Abellaneda, J. M.; Sáez‐Acosta, A.; Mrowiec, A.; Pallarés, F. J.
Abstract : Genetic susceptibility or resistance to diseases is currently drawing increasing attention. This work describes two different breeding herds showing signs of periweaning failure‐to‐thrive syndrome (PFTS), an emergent swine disease. The disease was diagnosed based on clinical picture and confirmed by histopathology. The possibility of main infectious pathogens was ruled out by immunohistochemistry and PCR. In a simple approach, sires of the affected piglets have been determined using microsatellite paternity analysis, including a healthy group in each case. In each of the two farms, a single boar was found to have sired 45–50 per cent sick animals. Removal of this sire from two farms resulted in a significant decrease in the prevalence of the disease among the offspring, in accordance with other two cases diagnosed, although without including a control group. Since the analysed animals belonged to three different genetic lines, these findings point to the existence of individual genetic susceptibility to this syndrome.